Is PROGRESA working? summary of the results of an evaluation by IFPRI - Skoufias, Emmanuel; McClafferty, Bonnie (International Food Policy Research Institute, 2001)
This document summarizes 24 months of extensive research by the International Food Policy Research Institute designed to evaluate whether PROGRESA has been successful at achieving its goals. The evaluation analyzes what has been the impact of PROGRESA on education, health, and nutrition as well as in other areas, such as women’s status and work incentives.